A circulating subset of BRAFV600E‐positive cells in infants with high‐risk Langerhans cell histiocytosis treated with BRAF inhibitors. (26th July 2021) - Poch, Rita; Le Louet, Solenne; Hélias‐Rodzewicz, Zofia; Hachem, Nawa; Plat, Geneviève; Barkaoui, Mohamed‐Aziz; Lapillonne, Hélène; Delhommeau, François; Emile, Jean‐François; Donadieu, Jean; Héritier, Sébastien
Summary: BRAF inhibitors are an effective treatment for BRAF V600E ‐mutated, risk‐organ‐positive Langerhans cell histiocytosis (RO + LCH). However, cell‐free BRAF V600E DNA often persists during therapy and recurrence frequently occurs after therapy discontinuation. To identify a pathological reservoir of BRAF V600E ‐mutated cells, we studied peripheral blood cells obtained from six infants with RO + multisystem (MS) LCH that received targeted therapy. After cell sorting, the BRAF V600E mutation was detected in monocytes ( n = 5), B lymphocytes ( n = 3), T lymphocytes ( n = 2), and myeloid and plasmacytoid dendritic cells ( n = 2 each). This biomarker may offer an interesting tool for monitoring the effectiveness of new therapeutic approaches for weaning children with RO + LCH from targeted therapy.